Compromised vitamin D status negatively affects muscular strength and power of collegiate athletes - Hildebrand, R. A.; Miller, B.; Warren, A.; Hildebrand, D.; Smith, B. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Increasing evidence indicates that compromised vitamin D status, as indicated by serum 25-hydroxyvitamin D (25-OH D), is associated with decreased muscle function. The purpose of this study was to determine the vitamin D status of collegiate athletes residing in the southern U.S. and its effects on muscular strength and anaerobic power. Collegiate athletes (n = 103) from three separate NCAA athletic programs were recruited for the study. Anthropometrics, vitamin D and calcium intake, and sun exposure data were collected along with serum 25-OH D and physical performance measures (Vertical Jump Test, Shuttle Run Test, Triple Hop for Distance Test and the 1 Repetition Maximum Squat Test) to determine the influence of vitamin D status on muscular strength and anaerobic power. Approximately 68% of the study participants were vitamin D adequate (>75 nmol/L), whereas 23% were insufficient (75-50 nmol/L) and 9%, predominantly non-Caucasian athletes, were deficient (<50 nmol/L). Athletes who had lower vitamin D status had reduced performance scores (p < .01) with odds ratios of 0.85 on the Vertical Jump Test, 0.82 on the Shuttle Run Test, 0.28 on the Triple Hop for Distance Test, and 0.23 on the 1 RM Squat Test. These findings demonstrate that even NCAA athletes living in the southern US are at risk for vitamin D insufficiency and deficiency and that maintaining adequate vitamin D status may be important for these athletes to optimize their muscular strength and power.